Arf1 and Arf6 Promote Ventral Actin Structures formed by acute Activation of Protein Kinase C and Src - Caviston, Juliane P. (Cytoskeleton (Hoboken), 2014)
Arf proteins regulate membrane traffic and organelle structure. Although Arf6 is known to initiate actin-based changes in cell surface architecture, Arf1 may also function at the plasma membrane. Here we show that acute activation of protein kinase C (PKC) induced by the phorbol ester PMA led to the formation of motile actin structures on the ventral surface of Beas-2b cells, a lung bronchial epithelial cell line. Ventral actin structures also formed in PMA-treated HeLa cells that had elevated levels of Arf activation. For both cell types, formation of the ventral actin structures was enhanced by expression of active forms of either Arf1 or Arf6, and by the expression of guanine nucleotide exchange factors that activate these Arfs. By contrast, formation of these structures was blocked by inhibitors of PKC and Src, and required phosphatidylinositol 4, 5-bisphosphate, Rac, Arf6 and Arf1. Furthermore, expression of ASAP1, an Arf1 GTPase activating protein (GAP) was more effective at inhibiting the ventral actin structures than was ACAP1, an Arf6 GAP. This study adds to the expanding role for Arf1 in the periphery and identifies a requirement for Arf1, a “Golgi Arf”, in the reorganization of the cortical actin cytoskeleton on ventral surfaces, against the substratum.